Gamification on Users Daily Activities - José Carlos Portela Pereira (2014)
Mobile applications increasingly play an essential role on people's lives, they help us to perform tasks more efficiently that make part of our day-to-day. The ease of access for developing such applications has led to our disposal a wide range of applications that envolve areas such as healthcare, leisure, education , etc.Gamification is the use of mechanical game design concepts applied in non-game contexts in order to make an activity more interesting. This technique has been adopted in recent years by a lot of services in order to increase the user involvement with the platform itself. This concept is applied in many non-game contexts and physical activity is no exception. Actually, this concept has obtained a lot of sucess in this area since users improve their health while challenging themselves or other users within the network.This dissertation aims to prove how Gamification can be used in order to encourage the practice of physical activity. With this intention, a platform was developed which is constituted by a Web application that allows the creation of gamified elements that subsequently are sent to a mobile application which challenge and promotes their users to improve their levels of physical activity. Machine learning algorithms were integrated in the platform in order to adapt the application to different type of users.